Islamic Law Review on Fintech P2P Lending, Regulations and Its Institutions In Indonesia - Susamto, Burhanuddin; Akbar, Akhmad; Tajuddin, M. Maulana (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 3 No 1 (2022): Proceeding of International Conference on Engineering, Technology, and Social Sciences, 2023)
This article aims to review fintech P2P lending in Indonesia from the perspective of Islamic law.  P2P lending has great potential to support financial inclusion in the context of economic empowerment from various layers. However, if this P2P lending practice is not accompanied by adequate legal instruments, this financing model will have a high risk. Legal protection needs to be given to all parties involved in this transaction proportionally.  Islamic law needs to review the practice of P2P lending in Indonesia so that in the future it can provide more benefits to the community. From the results of the review, it was found that there are no regulations that support the establishment of Islamic P2P lending. The P2P lending concept cannot accommodate sharia contracts that can be applied to fintech financing. Islamic P2P lending companies in Indonesia are still few compared to conventional ones, and even there is no guarantee of complying with sharia principles.